2019
DOI: 10.1186/s12931-019-1204-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical pleurodesis – a review of mechanisms involved in pleural space obliteration

Abstract: Chemical pleurodesis is a therapeutic procedure applied to create the symphysis between the parietal and visceral pleura by intrapleural administration of various chemical agents (e.g. talk, tetracycline, iodopovidone, etc.). The two major clinical conditions treated with chemical pleurodesis are recurrent pleural effusion (PE) and recurrent spontaneous pneumothorax. Although the history of chemical pleurodesis began over a century ago, detailed data on the mechanisms of action of sclerosing agents are highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 134 publications
1
39
0
1
Order By: Relevance
“…While the possibility that small apical radiographically occult pneumothoraces may have been present, an alternative explanation may lie in the current or prior pulmonary inflammatory process, which can form pleural adhesions between parietal and visceral layers of the pleura. Such adhesions can protect against development of pneumothoraces, as illustrated by the concept of pleurodesis in which the pleural space is artificially obliterated and subsequently adhesed to treat recurrent spontaneous pneumothorax [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the possibility that small apical radiographically occult pneumothoraces may have been present, an alternative explanation may lie in the current or prior pulmonary inflammatory process, which can form pleural adhesions between parietal and visceral layers of the pleura. Such adhesions can protect against development of pneumothoraces, as illustrated by the concept of pleurodesis in which the pleural space is artificially obliterated and subsequently adhesed to treat recurrent spontaneous pneumothorax [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1, IL-6, IL-8, interleukin 1, 6 and 8; PVP-I, iodopovidone; TGF-β, transforming growth factor β fluid correlated negatively with pleural fluid tPA levels (Cl et al, 2005). That may suggest that IL-1β is an important player in inflammation, fibrosis, and coagulation pathways activated in the process of pleurodesis (Mierzejewski et al, 2019). Pro-inflammatory mesothelial response manifested by tendency in increasing IL-1β protein production found in our study seems to be in line with the above considerations and suggests the role of IL-1β in the formation and maintenance of the inflammatory response in the course of pleurodesis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other cell populations including neutrophils, fibroblasts, and macrophages are involved. IL-8 and neutrophils seem to be critically important in the initiation and maintenance of pleural inflammation (Psathakis et al, 2006) Numerous other mediators have also been shown to play a role in this process, including TGF-β, basic fibroblast growth factor (bFGF), and pro-inflammatory cytokines IL-6, IL-1 (Mierzejewski et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As sclerosant agents, tetracycline, talc, iodopovidone are used to achieve chemical pleurodesis by triggering an inflammatory response [17,18]. According to Rice et al and Mc-Carthy et al, local tetracycline application had no effect on seroma formation after mastectomy and was associated with severe pain [19,20].…”
Section: Discussionmentioning
confidence: 99%